1987
DOI: 10.1007/bf00606641
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic differences in the inhibitory effect of cimetidine on the metabolism of antipyrine

Abstract: The relationship between acetylator phenotype and the inhibitory effect of cimetidine on the hepatic metabolism of antipyrine has been studied in 20 subjects. Cimetidine, 1,0 g/day resulted in a significant decrease in the metabolic clearance rate of antipyrine, but only in slow acetylators, as fast acetylators were less affected. No sex difference was observed. No major change occurred in the urinary excretion of D-glucaric acid, which means that cimetidine had not-affected that Phase II reaction. It did sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
2
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…From the AP metabolite data it is evident that the cumulative excretion and CLm of NORA were significantly lower in the presence of cimetidine (Table lb). These data on AP metabolism during cimetidine coadministration are similar to those from many previous reports (Teunissen et al, 1985;Gachalyi et al, 1987;Labs, 1988). Recently cimetidine pretreatment was reported to decrease the elimination rate of TMO when incubated with rat liver microsomes (Tanaka & Misawa, 1985;Tanaka et al, 1986b).…”
Section: Discussionsupporting
confidence: 90%
“…From the AP metabolite data it is evident that the cumulative excretion and CLm of NORA were significantly lower in the presence of cimetidine (Table lb). These data on AP metabolism during cimetidine coadministration are similar to those from many previous reports (Teunissen et al, 1985;Gachalyi et al, 1987;Labs, 1988). Recently cimetidine pretreatment was reported to decrease the elimination rate of TMO when incubated with rat liver microsomes (Tanaka & Misawa, 1985;Tanaka et al, 1986b).…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported by Dossing et al (1993). In contrast, Gasachalyi et al, (1987) found that cimetidine decreased only the partial clearance of norantipyrine. Back et al (1988) reported, that cimetidine caused at least a 30% decrease in the clearance of each of the metabolites, but was statistically significant only for HMA.…”
supporting
confidence: 85%
“…The latter finding may perhaps be due to the increase in the apparent volume of distribution. A similar increase in the distribution volume of antipyrine in the presence of cimetidine was found by Gasachalyi et al (1987).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…It has been shown that such treatments are of sufficient duration to inhibit liver microsome activity (Cimetidine: Jackson et al, 1981;Grygiel et al, 1984;Jonkman and Upton, 1984;Cusack et al, 1985 ;Gachalyi et al, 1987. Troleandomycin: Weinberger et al, 1976Lavarenne et af., 1981 ;Jonkman and Upton, 1984;Brazier et at., 1980;Ketoconazole: Brown et af., 1985).…”
Section: Protocolmentioning
confidence: 99%